2019
DOI: 10.1175/jcli-d-18-0562.1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Differences in Bucket Sea Surface Temperature Measurements among Nations Identified Using a Linear-Mixed-Effect Method

Abstract: The International Comprehensive Ocean–Atmosphere Dataset (ICOADS) is a cornerstone for estimating changes in sea surface temperatures (SST) over the instrumental era. Interest in determining SST changes to within 0.1°C makes detecting systematic offsets within ICOADS important. Previous studies have corrected for offsets among engine room intake, buoy, and wooden and canvas bucket measurements, as well as noted discrepancies among various other groupings of data. In this study, a systematic examination of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Gridded global instrumental surface temperature data sets presently stretch to 1850, with estimates of uncertainty available that include both the effect of sampling uncertainty and systematic changes in measurement techniques, such as different types of buckets (Folland and Parker 1995). While the record is fairly well researched, issues continue to be discovered, such as an inhomogeneity in SST data in the 1940s (Thompson et al 2008); and ongoing offsets due to differences in observing fleets (Chan and Huybers 2019). Long, homogenized instrumental surface temperature records go back to the 18th century for some European locations such as Milan, Stockholm, and Central England, resolving daily variability (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gridded global instrumental surface temperature data sets presently stretch to 1850, with estimates of uncertainty available that include both the effect of sampling uncertainty and systematic changes in measurement techniques, such as different types of buckets (Folland and Parker 1995). While the record is fairly well researched, issues continue to be discovered, such as an inhomogeneity in SST data in the 1940s (Thompson et al 2008); and ongoing offsets due to differences in observing fleets (Chan and Huybers 2019). Long, homogenized instrumental surface temperature records go back to the 18th century for some European locations such as Milan, Stockholm, and Central England, resolving daily variability (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…To what extent this discrepancy is due to model error, residual forcing or remaining observational error in SSTs (Chan andHuybers 2019, Haustein et al 2019) is presently unclear (Friedman et al in revision). The difference between variability with multimodel mean removed compared to that from control simulations ( figure 8(c)) suggests that residual forcing may have contributed to the variability in observations.…”
Section: Is Decadal Climate Variability Realistic In Climate Models?mentioning
confidence: 99%
“…In contrast, Kent and Kaplan (2006) and Carella, Morris, et al (2017) focused on situations in which solar heating was negligible. Recently, Chan and Huybers (2019) showed that there are relative biases between bucket measurements made by ships from different countries and between bucket measurements found in different decks in ICOADS. They argue that correcting for biases between decks and nations should improve estimated SSTs.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
“…Recent work by others has included the examination of biases in different types of buckets (e.g. Carella et al ., 2017; Chan and Huybers, 2019).…”
Section: Data Production Methodsmentioning
confidence: 99%